Formation of gold nanoparticles in silicon suboxide films prepared by plasma enhanced chemical vapour deposition - Chan, K.; Aspanut, Z.; Goh, B.; Muhamad, M.R.; Rahman, S.A. (2011)
Nanostructured materials fabricated by dispersing metal particles on the dielectric surface have potential application in the field of nanotechnology. Interfacial metal particles/dielectric matrix interaction is important in manipulating the structural and optical properties of metal/dielectric films. In this work, a thin layer of gold (Au) was sputtered onto the surface of silicon oxide, SiO(x) (0.38<x<0.68) films which was deposited at different N(2)O/SiH(4) flow rate ratios of 5 to 40 using plasma enhanced chemical vapor deposition (PECVD) technique prior to the annealing process at 800 degrees C. FTIR spectra demonstrate the intensity and full-width at half-maximum (FWHM) of Si-O-Si stretching peaks are significantly dependent on the N(2)O/SiH(4) flow-rate ratio, eta. The films deposited at low and high N(2)O/SiH(4) flow rate ratios are dominated by the oxygen and silicon contents respectively. The size and concentration of Au particles distributed on the surface of SiOx films are dependent on the N(2)O/SiH(4) flow-rate ratio. High concentrations of Au nanoparticles are distributed evenly on the surface of the film deposited at N(2)O/SiH(4) flow-rate ratio of 30. Crystallinity and crystallite sizes of Au are enhanced after the thermal annealing process. Appearance of surface plasma resonance (SPR) absorption peaks at 524 nm for all samples are observed as a result of the formation of Au particles. The annealing process has improved SPR peaks for all the as-deposited films. The energy gap of the as-deposited Au/SiO(x) films are in the range of 3.58 to 4.38 eV. This energy gap increases after the thermal annealing process except for the film deposited at eta = 5. (C) 2011 Elsevier B.V. All rights reserved.